Total suction measurement of unsaturated soils with a device using the chilled-mirror dew-point technique - Leong, Eng Choon (2011)
The total suction of a soil consists of two components: matric suction and osmotic suction. There are different techniques for measuring the total, matric and osmotic suction. The total suction of the soil is related to the water vapour pressure in the air space of the soil, and can be measured by devices capable of measuring relative humidity. A range of devices is available to measure relative humidity. In this paper, a device using the chilled-mirror dew-point technique with a selectable temperature environment was used to measure the relative humidity of a soil sample. Two residual soils of Singapore were used in the evaluation of the device for total suction measurement. The residual soils were compacted at various water contents and with three compaction efforts to provide soil samples of various suction values. The total suction of the compacted soil was measured and compared with its matric and osmotic suctions as independently measured using the null-type axis-translation apparatus and the pore fluid squeezer respectively. The time to equilibrium to obtain the total suction of the soil samples varied between a couple of minutes to about 18 min. The test results show that total suctions obtained using the device are always greater than the sum of the matric and osmotic suctions measured independently. The discrepancy increases as suction increases and is attributed to the limitations of the device for measuring the relative humidity of the soil samples accurately. However, by accounting for the discrepancy, the device can be used as a rapid means of determining the total suction of unsaturated soils.